TALKING CIRCLE TO IMPROVE STUDENTS’ SPEAKING ABILITY - Lukman Hakim (LPPM UNISDA, 2022)
Abstract : The research in title Talking Circle to Improve Students’ Speaking Ability aims : (1). To know how the teaching and learning of speaking which focused on language components using talking talking circle is, and (2). To describe the improvement of the junior high school students’ speaking ability. This research used a qualitative with Classroom Action Research (CAR). The subjects of this research were 19 students of class IX SMP Muhammadiyah 27 Paciran Lamongan. The data was obtained from the process of teaching and learning by the tecnique of observation through observation sheet and vidio recording. The result of this research showed that the process of teaching and learning which focused on four language components using talking circle strategy could run well and the students’ speaking ability improved as well.